2012
DOI: 10.3329/afj.v4i0.12942
|View full text |Cite
|
Sign up to set email alerts
|

Technology and the Language Teacher

Abstract: Today is the world of Facebook, Twitter, MySpace, Google, Yahoo, I-pods, I- pads. Gadgets reign supreme even in a developing country like Bangladesh (e.g. cell phones) and so technology is fused in every part of our lives, in fact, “technology is no longer a tool to create an alternative environment- it is THE environment” (Gupta, 2010: 68). Academic institutions are, therefore, expected to prepare students for a technological era that awaits them. As an inevitable consequence, there is an expectation from adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Thus, in terms of the imitations of such technology-enhanced EFL reading classes in Bangladesh, valuable insights are obtained from the quantitative and qualitative findings. Here, some of the current limitations of the implementation of technology in the higher secondary EFL reading context are like those noted in the aforementioned study by Ivy (2012) in terms of lack of teacher training and expertise in technology use, lack of students' expertise in technology use, lack of maintenance, lack of diverse technology due to budgetary issues, etc. However, more EFL context-specified limitations are also unraveled by the findings.…”
Section: Limitations Of Technology-enhanced Efl Reading Classesmentioning
confidence: 69%
See 1 more Smart Citation
“…Thus, in terms of the imitations of such technology-enhanced EFL reading classes in Bangladesh, valuable insights are obtained from the quantitative and qualitative findings. Here, some of the current limitations of the implementation of technology in the higher secondary EFL reading context are like those noted in the aforementioned study by Ivy (2012) in terms of lack of teacher training and expertise in technology use, lack of students' expertise in technology use, lack of maintenance, lack of diverse technology due to budgetary issues, etc. However, more EFL context-specified limitations are also unraveled by the findings.…”
Section: Limitations Of Technology-enhanced Efl Reading Classesmentioning
confidence: 69%
“…The research also showed that the students benefited significantly from reading texts on mobile technology due to its easy accessibility to most of the learners. However, Ivy's (2012) research on the limitations of EFL classes in Bangladesh, in general, asserted problems with insufficient teacher training and practice in the use of technology. There were logistic issues with maintenance and troubleshooting as well.…”
Section: Introductionmentioning
confidence: 99%
“…g) Electronic whiteboard: Electronic whiteboard or the smart board is the latest addition to the technologies used in classroom. However, Ivy (2011) states, "Although it is a very interesting add on to the classroom, implementation is costly and as such is not feasible in the context of Bangladesh" (p.213).…”
Section: B)mentioning
confidence: 99%